Akuntabilitas dan Trasparansi Pengelolaan Keuangan Partai Politik (Studi Kasus DPC Partai Demokrat Provinsi Sulawesi Tengah) - Mappanyukki, Andi; Vinny Anggitresia, Thalia; Oktaviani Sultan, Resky; Maharani, Adinda; Suci Rahmadani, Indah; Pattawe, Abdul; Kahar, Abdul; Usman, Ernawaty (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2025)
This study aims to understand how political party administrators understand political party financial reporting. In addition, it continues with a discussion on understanding the principles of transparency and accountability in political party financial reporting. The object of research in this study is the branch representative council (DPC) of the Democratic Party of Central Sulawesi Province. This qualitative study uses a phenomenological approach, data collection techniques using interviews, documentation, and direct observation. The results of the study show that: The understanding of political party administrators in the Democratic DPC of Central Sulawesi Province regarding financial reporting obligations according to Law Number 2 of 2011 is quite good. The Democratic DPC of Central Sulawesi Province has also presented financial reports according to Article 39 of Law Number 2 of 2011 concerning Political Parties. In terms of transparency and accountability, political parties have presented financial reports that can meet these criteria. However, this study also found that the transparency aspect in political party financial reporting is still not optimal.